The Clinical Evaluation and Survival Rate of Pediatric Sarcoma in Dr. Sardjito General Hospital, Yogyakarta, Indonesia - Mulatsih, Sri; Hanifah, Atikah; Oktasari, Rizki (Indonesian Journal of Cancer, 2024)
Background: Pediatric sarcoma is a heterogeneous group of tumors and accounts for approximately 10% of childhood solid tumors. The most common soft tissue sarcoma is rhabdomyosarcoma, and the most common bone sarcomas are osteosarcoma and Ewing’s sarcoma. The prognosis for children with sarcoma depends on age, primary tumor site, tumor size, resectability, presence or absence of metastases, number of metastatic sites, presence or absence of regional lymph node involvement, histopathologic subtype, and in some cases, delivery of radiation therapy. This study aims to evaluate clinical signs, symptoms, and survival rates.Methods: We carried out a retrospective analysis of clinical data from sarcoma patients in Dr. Sardjito General Hospital to provide a reference for the design of future pediatric sarcomaspecific studies. Data from patients with sarcoma entered in Dr. Sardjito General Hospital from 2012 until 2017 was collected. Patients who had confirmed pediatric sarcoma diagnosis were eligible for samples at study entry. Clinical manifestations were assessed, and overall survival was calculated with Kaplan-Meier.Results: Among 400 patients coding with pediatric sarcoma, 154 were excluded because their medical records were broken and deleted, and 82 because the coding was not related to their diagnosis (non-pediatric sarcoma). Sixty patients were eligible for the analysis (28 men and 32 women, median age at diagnosis 13 years, range 0–18 years). Fifteen patients (25%) received chemotherapy, radiation, and surgery as a treatment, 16 patients (26.67%) received chemotherapy and surgery only, five patients (8.33%) received chemotherapy only, five patients (8.33%) received chemotherapy and radiation only, one patient (1.67%), and ten patients (16.67%) received surgery only. The most common primary tumor was located in the lower extremity (n = 29; 48.33%). At entry, metastases were mainly found in the lungs. The overall survival rate of pediatric sarcoma in Dr. Sardjito General Hospital was 19% or 88 months (95% CI median 48 months ± 4.658).Conclusions: This study revealed a diverse range of clinical presentations and a concerningly low overall survival rate. These findings highlight the need for further research to improve treatment strategies and outcomes for pediatric sarcoma, particularly focusing on factors influencing survival and addressing the high rate of metastatic disease.